Agricultural intensification alters marbled newt genetic diversity and gene flow through density and dispersal reduction. Issue 1 (8th November 2021) - Gauffre, Bertrand; Boissinot, Alexandre; Quiquempois, Vincent; Leblois, Raphael; Grillet, Pierre; Morin, Sophie; Picard, Damien; Ribout, Cécile; Lourdais, Olivier
Abstract: Recent agricultural intensification threatens global biodiversity with amphibians being one of the most impacted groups. Because of their biphasic life cycle, amphibians are particularly vulnerable to habitat loss and fragmentation that often result in small, isolated populations and loss of genetic diversity. Here, we studied how landscape heterogeneity affects genetic diversity, gene flow and demographic parameters in the marbled newt, Triturus marmoratus, over a hedgerow network landscape in Western France. While the northern part of the study area consists of preserved hedged farmland, the southern part was more profoundly converted for intensive arable crops production after WWII. Based on 67 sampled ponds and 10 microsatellite loci, we characterized regional population genetic structure and evaluated the correlation between landscape variables and (i) local genetic diversity using mixed models and (ii) genetic distance using multiple regression methods and commonality analysis. We identified a single genetic population characterized by a spatially heterogeneous isolation‐by‐distance pattern. Pond density in the surrounding landscape positively affected local genetic diversity while arable crop land cover negatively affected gene flow and connectivity. We used demographic inferences to quantitatively assess differences in effective population density and dispersal between the contrasted landscapes characterizing the northern and southern parts of the study area. Altogether, results suggest recent land conversion affected T . marmoratus through reduction in both effective population density and dispersal due to habitat loss and reduced connectivity.